2011
DOI: 10.3109/10837450.2010.550623
|View full text |Cite
|
Sign up to set email alerts
|

Quality by design approach in the optimization of the spray-drying process

Abstract: This study showed the applicability of DoE for the investigation of spray-dried powders. The knowledge of the interplay between process parameters and quality attributes will enable rational process design to achieve a desired outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…In contrast to our results, studies by Baldinger et al (2011) on the application of a two level full factorial design to the spray drying process of aqueous solutions with total solid concentration of 10% (w/v) containing a mixture of mannitol and trehalose in a mass ratio of 90:10 to produce inhalable dry powders, showed a poor linear relationship Page 13 of 42 A c c e p t e d M a n u s c r i p t between the observed and predicted values obtained for the evaluated responses, using 275 multivariate analysis as a statistical tool.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our results, studies by Baldinger et al (2011) on the application of a two level full factorial design to the spray drying process of aqueous solutions with total solid concentration of 10% (w/v) containing a mixture of mannitol and trehalose in a mass ratio of 90:10 to produce inhalable dry powders, showed a poor linear relationship Page 13 of 42 A c c e p t e d M a n u s c r i p t between the observed and predicted values obtained for the evaluated responses, using 275 multivariate analysis as a statistical tool.…”
Section: Resultscontrasting
confidence: 99%
“…39 In addition, inlet temperatures lower than 115°C and an ethanol ratio in aqueous solution lower than 30% generated a decrease in outlet temperature and, consequently, condensation inside the drying chamber. 40 Recent research has shown that submicron-sized microparticles are taken up rapidly by phagocytic cells in the synovium, whereas microspheres ranging in size from 3 µm to 60 µm remain dispersed in the joint cavity or adherent to the surface of the synovial membrane, and are well tolerated. However, microspheres in the smaller size range trigger a marked inflammatory response, causing joint swelling and loss of proteoglycans.…”
Section: Optimization Of Process Parametersmentioning
confidence: 99%
“…Vice versa, absorbance bands constitute a complicating factor for the determination of physical properties of the solid. Several studies have investigated the particle size in various processes (6,8,28,(30)(31)(32)(33) and the moisture content of lyophilized sugars and proteins by NIR (7,8,30,(34)(35)(36). However, NIR has seldom been applied to monitor the spray-drying process, and has rarely been used when proteins are the model system (37).…”
Section: Introductionmentioning
confidence: 99%